Retinal nerve fiber layer thickness in prematurity is correlated with stage of retinopathy of prematurity - Park, K-A (Eye (Lond), 2015)
PURPOSE: To compare retinal nerve fiber layer (RNFL) thickness profiles between preterm and full-term children and to investigate factors affecting the RNFL distribution in preterm children. METHODS: We performed Spectral domain optical coherence tomography (SD-OCT) peripapillary RNFL circular scan centered on the optic disc in 50 premature and 58 full-term children. RNFL thickness profiles were compared between preterm and full-term children using a linear regression model. Among preterm patients in this study, 20 patients previously received laser treatment for severe retinopathy of prematurity (ROP). RESULTS: Global average, nasal, and superior disc RNFL thickness profiles were significantly smaller in preterm children (92.70±16.57 μm, 56.02±17.04 μm, and 108.74±27.36 μm, respectively) compared with full-term children (101.63±9.21 μm, P=0.006, 69.14±14.15 μm, P<0.001, and superior, 129.11±18.14 μm, P<0.001, respectively). Multivariable analysis revealed that ROP stage was inversely correlated with nasal RNFL thickness (P=0.010). CONCLUSIONS: Our SD-OCT data demonstrate decreased global average, nasal, and superior disc RNFL thicknesses in preterm children. ROP stage was inversely correlated with nasal RNFL thickness. Further studies are needed to better understand the association between these structural changes and visual functions in preterm children.